Mapping modernity: The feminine middlebrow and the belle époque. (August 2014) - Holmes, Diana
Part of the remit of French Cultural Studies is surely to study the 'littérature de grande consommation' largely ignored by more canonical critical approaches, especially in France, but vital to the shaping of ideas and values. This article explores the aesthetics and function of the middlebrow novel ( roman de mœurs, roman d'idées ) at the belle époque, the period when technology and cross-class demand for entertaining and instructive fictions converged to produce a golden age of publishing. The main focus is on middle-class women as readers; contrary to modernist orthodoxy, I argue that the mainstream, formally conventional 'middlebrow' novel, at least in the hands of women authors, could perform a radicalising function, bringing 'new woman' plots into respectable drawing-rooms, offering pleasurably immersive stories that quietly confronted readers with the gap between Republican values and the reality of sexual inequality, and welcomed modernity as an age of potential for women.